Estimation of Recirculation in Arterio-Venous Fistula among Haemodialysis Patients (Bangladesh Journal of Medicine, 2015)
Recirculation in haemodialysis patients is an important factor as it is a correctable cause of under dialysis. This study was a cross sectional study done in the department of Nephrology Dhaka Medical College and hospital during the period Sept 2010 to Oct 2011 with a view to estimate recirculation in AV fistula among the Haemodialysis patients. This study used two needle urea based method for estimation of recirculation. Total 118 patients were included in this study.Bangladesh J Medicine Jan 2014; 25 (1) : 17-20